The blind’s profile in the municipality of Sobral/CE - Escócio, Jamille; Caetano, Joselany Áfio; Soares, Enedina (Rev Rene, 2004)
This is a descriptive study that involved 63 blind people who live in the urban zone of the city of Sobral/CE that aimed at knowing their profile and the way they face adversities in their family life and society. The study was carried out from May 2002 to November 2003. Data were collected through home visits and free interviews. The outcomes show that most of the people studied are female (36); are older than 61 years old (40); have been having eye problems from 5 to 10 years (17); are adapting to the stigma (18); became blind as they got older (55); do not know the cause of their eye problem (23); became blind due to glaucoma and/or cataracts (18); find in their families support for treatment (25); said they need no self-help device (33). As a result, we can conclude that the nurse, when assisting this kind of client, shall define his profile in order to seek for strategies that contribute to health education as a way to insert the blind into society.